Armazenamento de sementes de soja dessecadas e avaliação da qualidade fisiológica, bioquímica e sanitária - Lacerda, André Luiz De Souza; Lazarini, Edson [UNESP]; Sá, Marco Eustáquio De [UNESP]; Valério Filho, Walter Veriano [UNESP] (Associação Brasileira de Tecnologia de Sementes, 2003)
The objective of the study was the evaluation of the physiologic, biochemical and sanitary characteristics of soybeans seeds after dessication with four dessicants, in different times, stored for six months and treated with fungicide. The experiment was carried out, in the Seed Laboratory, at UNESP - Ilha Solteira. The soybean plants of the cultivar IAC-15 were desiccated, in the agricultural year 1997/98, with: paraquat, diquat, paraquat + diquat (mixed in tank) and ammonium glufosinate at rates of 400, 300, 200+150 and 400 g.i.a. ha-1. starting in the R6 stage till R7, at five-day intervals. The seeds were harvested and placed in a dry chamber with relative humidity around 40% and temperature between 17 and 20ºC for six months. The analyses were carried out with non treated seeds and seeds treated with thefungicide thiabendazole (20 g.i.a/100 kg of seeds). The conclusions were: the seeds did not present enough physiologic qualities for commercialization, and the dessicant ammonium glufosinate presented, significantly, smaller germination values. The protein content was not affected by the dessication, however, for the ethereal extract there was reduction in this component in thes dessicated seeds. The product paraquat applied in the first times resulted in larger incidence of Fusarium spp. in the soybean seeds, while, for the Phomopsis spp. smaller indifferent incidence of the times of applications.

O trabalho teve o objetivo de avaliar as características fisiológicas, bioquímicas e sanitárias das sementes de soja colhidas após dessecação com quatro dessecantes, em diferentes épocas, armazenadas por seis meses e tratadas com um fungicida. O experimento foi realizado no Laboratório de Sementes da UNESP - Campus de Ilha Solteira. As plantas de soja do cultivar IAC-15 foram dessecadas, no ano agrícola 1997/98, com: paraquat, diquat, mistura paraquat + diquat e glufosinato de amônio, nas dosagens de 400, 300, 200+150 e 400 g.i.a./ha aplicados a partir do estádio R6 até R7, com intervalos de 5 dias. As sementes foram colhidas e acondicionadas em câmara seca, com umidade relativa em torno de 40% e temperatura entre 17 e 20ºC, por um período de seis meses. As análises foram realizadas com sementes tratadas com o fungicida thiabendazole (20 g.i.a./100 kg de sementes) e sementes não tratadas. Após análise e interpretação dos resultados obtidos, pode-se concluir que as sementes não apresentaram qualidades fisiológicas suficientes para comercialização. O tratamento com o dessecante glufosinato de amônio apresentou significativamente, menores valores de germinação. O teor de proteína não foi afetado pela dessecação, entretanto, para o extrato etéreo houve redução deste componente nas sementes dessecadas. O produto paraquat aplicado nas primeiras épocas resultou maior incidência de Fusarium spp., enquanto que, para o Phomopsis spp., menor incidência independente das épocas de aplicações.
Storage of dessicated soybean seed and the evaluation of physiologic, biochemical and sanitary characteristics
Keywords: soybean; storage; germination; vigour; healthy; soja; armazenamento; germinação; vigor; sanidade